Tingkat Pengetahuan Ibu tentang Infeksi Saluran Pernapasan Akut (ISPA) berhubungan dengan Kemampuan Merawat Balita dengan ISPA - A.A Bagus Suryantara; Made Rai Mahardika (LPPM STIKES Mataram, 2024)
Introduction: ISPA or often called acute respiratory infection is a disease that can be transmitted through droplets, contaminated objects and can also be transmitted through physical contact such as from hands. The prevalence of ISPA sufferers in Indonesia in 2023 will be 13.7%, occurring in the one to four year age group. Parental knowledge and ability to care for toddlers with ISPA is very important to prevent the occurrence of ISPA in toddlers. Objective: to determine the relationship between the mother's level of knowledge about ISPA and the ability to care for toddlers with ISPA. Method: This type of research is descriptive analytic correlational using a cross sectional approach. The population and sample of this study consisted of 94 respondents consisting of mothers with toddlers with sampling using simple random sampling techniques. Results: The research results showed that the majority of respondents had relatively high knowledge about ISPA (71.3%) and the majority of respondents were able to care for toddlers with ISPA as much as 55.3%. In the analysis test using chi square, the value of p = 0.006 (p<0.005) was obtained. Conclusion: The conclusion of this research is that there is a relationship between the mother's level of knowledge about ISPA and the ability to care for toddlers with ISPA in the work area of Kuta II Community Health Center.